2019
DOI: 10.1186/s12916-019-1366-x
|View full text |Cite
|
Sign up to set email alerts
|

Why we need a small data paradigm

Abstract: Background There is great interest in and excitement about the concept of personalized or precision medicine and, in particular, advancing this vision via various ‘big data’ efforts. While these methods are necessary, they are insufficient to achieve the full personalized medicine promise. A rigorous, complementary ‘small data’ paradigm that can function both autonomously from and in collaboration with big data is also needed. By ‘small data’ we build on Estrin’s formulation and refer to the rigor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 33 publications
1
99
0
Order By: Relevance
“…In general, researchers in the field have considered that the deep learning methods are suitable for analyzing large datasets and the majority of studies have been conducted with bigdata [48]. Even if this might be the case in general, several researchers, for example, those who are interested in applying the deep learning methods in medical and clinical science, have been trying to test whether the methods can contribute to improving automatized diagnosis procedures with relatively small datasets [49]. In their studies, they have found that even with small datasets, the deep learning methods can more accurately predict clinical outcomes compared with traditional analysis methods and they can be well used in the aforementioned context dealing with small datasets [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…In general, researchers in the field have considered that the deep learning methods are suitable for analyzing large datasets and the majority of studies have been conducted with bigdata [48]. Even if this might be the case in general, several researchers, for example, those who are interested in applying the deep learning methods in medical and clinical science, have been trying to test whether the methods can contribute to improving automatized diagnosis procedures with relatively small datasets [49]. In their studies, they have found that even with small datasets, the deep learning methods can more accurately predict clinical outcomes compared with traditional analysis methods and they can be well used in the aforementioned context dealing with small datasets [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate properties that are commonly found across other wearable sensor data, which are increasingly gaining in popularity (3). In order to effectively integrate such data with personalized medicine and health in the future, we must understand how specific timings and types of interventions impact individual patients (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…The wearable sensor market was valued at $10.8 billion USD in 2019 and is expected to triple in value over the next five years (1). Investment is bolstered by the great potential for advancing personalized medicine in the near future (2)(3)(4). Whereas medicine has previously focused on determining the right interventions, it is now more focused on for whom and when (5).…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a significant movement underway to develop interactive research tools that can support public health advocacy and environmental justice. Examples include (1) the United States Department of Agriculture (USDA) food desert locator [98], (2) Environmental Protection Agency environmental justice tools [51], and (3) some of the dynamic neighborhood/environmental mapping work performed at the University of California, San Diego [99][100][101].…”
Section: Neighborhoodsmentioning
confidence: 99%